Parachiloglanis bhutanensis, a new species of torrent catfish (Siluriformes:Sisoridae) from Bhutan - Thoni, R. J.; Gurung, D. B. (Zootaxa, 2014)
Parachiloglanis bhutanensis is a newly discovered species of torrent catfish from eastern Bhutan. With its discovery, the genus Parachiloglanis is no longer monotypic. The species differs from Parachiloglanis hodgarti in meristic, mensural, and coloration characters. Parachiloglanis bhutanensis is confirmed as a member of the genus by the absence of a post-labial grove on the lower lip, which is present in other genera of the subfamily Glyptosterninae (as either complete or incomplete). It is diagnosed within the genus by the presence (versus absence) of a series of 35–40 large white pores along the lateral line, a tall adipose fin (roughly two times the height of the adipose fin in P. hodgarti), a less dorsoventrally flattened body than P. hodgarti, a deeper head, wider mouth, longer inner- and outer-mandibular barbels, a truncate (versus indented to lunate) caudal fin, and the absence (versus presence) of black and white pigmentation on the caudal fin.